Development of Aloe Vera – Turmeric Tablets Formulation as a Food Product - Halim, Nurul Syahirah; Mat Ali @ Yunus, Zalilah Murni (Enhanced Knowledge in Sciences and Technology, 2021)
Aloe vera (AV) and turmeric (T) were used in the development of chewable tables due to their high therapeutical benefit upon consumption. The objective of this study is to produce and evaluate the Aloe vera powder (AVP), to formulate chewable tablets with better quality control and taste-masking properties and also to investigate the quality control test, sensory acceptance and Antioxidant activity of the AV-T tablets. Granule properties play an important role in the final performance of a tablet. A consistent flow of granulation provides the required avenues to control tablet weights. Then, consistent tablet weight can result in repeatable tablet hardness, contributing to end product uniformity. Hence, this study on the development of AV-T tablets will be focused on the formulation of chewable tablets with better quality control and taste masking properties. A dehydrator was used in achieving a physical stable of powdered form AVG. The AVP was compared with commercialized AVP (CAVP) to measure the physicochemical properties efficiency prior to tableting the tablets. The formulation on the AV-T tablet using the simplex lattice design method with the alteration between Microcrystalline cellulose (MCC) and mannitol (M) was conducted to aid in the development of a chewable AV-T tablet with better disintegration and taste-masking quality. The correlation between the physicochemical properties and quality control of the tablets also was studied. The alteration effects of MCC and mannitol also will be studied in this research. Lastly, sensory and antioxidant activity will be conducted. The result from the analysis showed that there was a significant difference in the alteration of both MCC and mannitol on both formulations, and also between the physicochemical characteristic of AVP and CAVP. MCC concentration also was observed in scavenging free radicals. No significant difference observed in sensory attributes except for sweetness (p< 0.05). The TPC and TFC result also corresponds with the inhibition percentage of free radicals.